Epidermal Growth Factor Receptor and Transforming Growth Factor β Signaling Pathways Cooperate To Mediate Chlamydia Pathogenesis - Igietseme, Joseph U. (Infect Immun, 2020)
Human genital Chlamydia infection is a major public health concern due to the serious reproductive system complications. Chlamydia binds several receptor tyrosine kinases (RTKs) on host cells, including the epidermal growth factor receptor (EGFR), and activates cellular signaling cascades for host invasion, cytoskeletal remodeling, optimal inclusion development, and induction of pathogenic epithelial-mesenchyme transition (EMT). Chlamydia also upregulates transforming growth factor beta (TGF-β) expression, whose signaling pathway synergizes with the EGFR cascade, but its role in infectivity, inclusions, and EMT induction is unknown. We hypothesized that the EGFR and TGF-β signaling pathways cooperate during chlamydial infection for optimal inclusion development and stable EMT induction. The results revealed that Chlamydia upregulated TGF-β expression as early as 6 h postinfection of epithelial cells and stimulated both the EGFR and TGF-β signaling pathways. Inhibition of either the EGFR or TGF-βR1 signaling substantially reduced inclusion development; however, the combined inhibition of both EGFR and TGF-βR1 signaling reduced inclusions by over 90% and prevented EMT induction. Importantly, EGFR inhibition suppressed TGF-β expression, and an inhibitory thrombospondin-1 (Tsp1)-based peptide inhibited chlamydia-induced EMT, revealing a major source of active TGF-β during infection. Finally, TGF-βR signaling inhibition suppressed the expression of transforming acidic coiled-coil protein-3 (TACC3), which stabilizes EGFR signaling, suggesting reciprocal regulation between TGF-β and EGFR signaling during chlamydial infection. Thus, RTK-mediated host invasion by chlamydia upregulated TGF-β expression and signaling, which cooperated with other cellular signaling cascades and cytoskeletal remodeling to support optimal inclusion development and EMT induction. This finding may provide new targets for chlamydial disease biomarkers and prevention.